2017
DOI: 10.1016/j.jhazmat.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of controlled release formulations of diuron and alachlor herbicides on the biochemical activity of agricultural soils

Abstract: The use of pesticides in agriculture is essential because it reduces the economic losses caused by pests, improving crop yields. In spite of the growing number of studies concerning the development and application of controlled release formulations (CRFs) of pesticides in agricultural soils, there are no studies about the effects of such formulations on the biochemical properties. In this paper the dissipation of diuron and alachlor in three agricultural soils for 127days, applied either as commercial or CRFs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 54 publications
(47 reference statements)
1
23
0
1
Order By: Relevance
“…Other data, however, suggested that slow‐release formulations of herbicides loaded into carriers, unlike their free forms, did not inhibit the growth of soil microbiota and stimulated enzymatic activity of soil. For instance, application of controlled‐release formulations of diuron and alachlor, loaded into phosphatidylcholine‐montmorillonite complex, enhanced dehydrogenase, phosphatase, and β‐glucosidase activity in soil . The addition of compost or sewage sludge to soil reduced the negative effects of herbicides on soil microorganisms …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other data, however, suggested that slow‐release formulations of herbicides loaded into carriers, unlike their free forms, did not inhibit the growth of soil microbiota and stimulated enzymatic activity of soil. For instance, application of controlled‐release formulations of diuron and alachlor, loaded into phosphatidylcholine‐montmorillonite complex, enhanced dehydrogenase, phosphatase, and β‐glucosidase activity in soil . The addition of compost or sewage sludge to soil reduced the negative effects of herbicides on soil microorganisms …”
Section: Resultsmentioning
confidence: 99%
“…For instance, application of controlled-release formulations of diuron and alachlor, loaded into phosphatidylcholine-montmorillonite complex, enhanced dehydrogenase, phosphatase, and -glucosidase activity in soil. 69 The addition of compost or sewage sludge to soil reduced the negative effects of herbicides on soil microorganisms. 70 The effects of the experimental herbicide formulations on soil microflora were studied.…”
Section: The Effects Of Herbicides On Soil Microfloramentioning
confidence: 99%
“…Application of pesticides is therefore a common and critical method to improve crop yield 35 . Of the tremendous amount of pesticides used, more than 99.7% persist and are accumulated in the environment 68 , undergoing various physicochemical catabolism and biodegradation processes which are closely associated with the composition and activity of soil microbial community 911 . Soil microorganisms have key functions in many vital soil processes, such as organic matter decomposition and nutrient cycling, and are responsible to a great extent for the function of soil ecosystems 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of modified clays in CRS for agriculture applications is widely reported in the literature [8][9][10]. Rytwo and Moshe [8] reported the use of montmorillonite modified with quaternary ammonium salts, such octadecyltrimethylammonium (ODTMA) and berberine, and other modifiers for the controlled release of allyl isothiocyanate (AITC), mustard oil major component used in the agriculture as fumigant in the control of insects.…”
Section: Introductionmentioning
confidence: 99%
“…The montmorillonite modification increased by at least 60% the time release of AITC. Tejada et al [9] studied the use of Na-montmorillonite modified with phosphatidylcholine (PC) for controlled release of the herbicides diuron and alachlor in soils. The dissipated amount of the herbicides in the soils using the PC-clay formulations was lower when compared with the direct herbicide application, mainly for alachlor in the first 16 days of incubation.…”
Section: Introductionmentioning
confidence: 99%